Memoria y hip hop, Una metáfora de origen (2021)
This article develops a reflection about Colombian, Latin American, and Ibero-American hip-hop, taking Peter Burke’s proposal of Cultural History as initial referent of analysis, in the framework of the researcher’s training in the Doctorate in Social Studies of the Universidad Distrital Francisco José de Caldas in the Memory, Experience, and Belief Line. A journey is proposed through the founding events of the appearance of hip-hop and its subsequent journey from the United States to other latitudes. From there, it proposes some metaphors of origin based on concepts such as trips, travelers, violence, gangsterism, music industry, among others. At the end, it raises some possibilities of analysis that contribute to the academic discussion about hip-hop, regarding the importance of memory in music studies.